2016
DOI: 10.15376/biores.11.2.4770-4780
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Mechanical Properties of Ultra-fine Cellulose-Filled Thermoplastic Epoxy Composites

Abstract: a Thermoplastic epoxy resin (TPER)-based composites containing different amounts of ultra-fine cellulose (UFC) were prepared via melt compounding and injection molding. The effect of UFC loading on the mechanical properties and dynamic rheological behavior of the UFC-filled TPER composites was analyzed. The UFC-filled composites displayed higher complex viscosities than those of the neat TPER composites, especially at low frequencies. The elastic modulus of the 20 wt.% UFC-filled composite was up to 6-and 2-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…While at intermediate shear rates, the network breaks down and cellulose aligns in the direction of shear . The rheological properties of the composites in this research are in good agreement with the behavior reported by other authors for cellulose‐based composites .…”
Section: Resultssupporting
confidence: 91%
“…While at intermediate shear rates, the network breaks down and cellulose aligns in the direction of shear . The rheological properties of the composites in this research are in good agreement with the behavior reported by other authors for cellulose‐based composites .…”
Section: Resultssupporting
confidence: 91%